Flat slab performance under loss of a corner column senario - Li, Rougang. (2011)
Abnormal loading events such as explosions, vehicle collisions, and foundation failure are not considered in an ordinary structural design. The local damage caused by such low-probability loads, however, may result in a chain reaction of structural element failure that leads to partial or even full collapse of a structure. The collapses of Ronan Point Tower in London in 1968 and the Alfred P. Murrah Fedural Building in Oklahoma City in 1995 have demonstrated the disastrous consequences of a progressive collapse due to extremely loading event; a structure must accommodate the initial local damage and develop an alternative load-path to sustain the redistributed loads. Despite notable experimental tests have been conducted in recent years, almost all of the laboratory tests studied the response of beam-column substructures under losing of interior or exterior column scenario. However, the loss of a corner column in the event of a terrorist attack is more prone to triggering progressive collapse than the loss of an interior column due to less secondary resistant branch (catenary and membrane action) can be relied on. Moreover, the corner bay (perimeter components) has much higher possibility being attacked by terrorism. Furthermore, it is known that flat slabs are more dangerous for progressive collapse compared to two-way slabs while limited experimental and analytical studies have been conducted to investigate the performance of reinforced concrete flat slabs subjected to losing corner column scenario. Thus, three flat slabs with varying slab reinforcement ratio are tested in current final year project to investigate the performance of RC flat slab for progressive collapse. The test results indicated that the tested flat slabs are vulnerable for progressive collapse. Punching failure in the corner column region and diagonal flexural failure occurred in the slab were two major failure mechanisms.